Pelaksanaan Kurikulum Merdeka Di SLB Negeri 2 Kota Padang: (Studi Deskriptif Kualitatif) - Novia Angel; Mega Iswari (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
This research discusses about. Implementation of the Independent Curriculum at SLB Negeri 2 Padang City. The purpose of this research is to find out opinions about the curriculum. Merdeka, to find out the preparations for implementation. Independent Curriculum, to find out the obstacles in implementing the Independent Curriculum and to find out how to overcome obstacles to the Independent Curriculum. This research uses a type of research with a qualitative descriptive method. By carrying out observations, documentation, and interviews to gather information about the implementation of the Independent Curriculum. The data obtained in the field is not written in the form of numbers or statistics but in the form of descriptions. narrative. The results of this study are that the Independent Curriculum is almost the same as the 13 Curriculum. In the Merdeka Curriculum, assessments are carried out individually, individual learning, for SLB that is the way of teaching. The way to teach Curriculum 13 is also almost the same as the way to teach the Independent Curriculum, as is the case with student projects for this project, schools have often applied it to children before the existence of the Independent Curriculum. From the interviews that the author has conducted, the obstacle for teachers in implementing the Independent Curriculum is that the Independent Curriculum has only just been implemented by the school so teachers are still in the learning process, both in preparing modules and preparing projects for children. With the passage of time the teacher hopes to understand more about the Independent Curriculum.